1999
DOI: 10.1074/jbc.274.45.32287
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Form of αB-crystallin Is Present in High Concentration in Some Human Cataractous Lenses

Abstract: Two unique polypeptides, 22.4 and 16.4 kDa, were prominent in some human cataracts. Both proteins were identified as modified forms of the small heat shock protein, ␣B-crystallin. The concentration of total ␣B-crystallin in most of these cataracts was significantly increased. The 22.4-kDa protein was subsequently designated as ␣B g . Mass spectrometric analyses of tryptic and Asp-N digests showed ␣B g is ␣B-crystallin minus the C-terminal lysine. ␣B g constituted 10 -90% of the total ␣B-crystallin in these cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
2
20
1
Order By: Relevance
“…Figure 3 shows that spot 5 is present in high concentrations in the 90-and 69-year individuals and, though less pronounced, is also elevated in the Soemmerring rings of the 51-and 79-year individuals. A high concentration of aB 1±174 , aB g , in some cataracts has been previously reported [9]. While aB 1±174 is not present in clear lens tissue at visually detectable levels using Coomassie blue stain, it has been detected in clear lenses by MS and is shown here to be detected when brightness and contrast are optimized in Fig.…”
Section: Analysis With Phoretix Software and Maldi-msmentioning
confidence: 50%
See 1 more Smart Citation
“…Figure 3 shows that spot 5 is present in high concentrations in the 90-and 69-year individuals and, though less pronounced, is also elevated in the Soemmerring rings of the 51-and 79-year individuals. A high concentration of aB 1±174 , aB g , in some cataracts has been previously reported [9]. While aB 1±174 is not present in clear lens tissue at visually detectable levels using Coomassie blue stain, it has been detected in clear lenses by MS and is shown here to be detected when brightness and contrast are optimized in Fig.…”
Section: Analysis With Phoretix Software and Maldi-msmentioning
confidence: 50%
“…Spot 5 consists of aB-crystallin residues 1±174, aB 1±174 , previously called aB g [9]. Figure 3 shows that spot 5 is present in high concentrations in the 90-and 69-year individuals and, though less pronounced, is also elevated in the Soemmerring rings of the 51-and 79-year individuals.…”
Section: Analysis With Phoretix Software and Maldi-msmentioning
confidence: 98%
“…Numerous studies have demonstrated that it is possible to induce in vitro, deamidation of asparagine residues (Robinson and Rudd, 1974;Tyler-Cross and Schirch, 1991;Fujii et al, 1999). Furthermore, it has been shown that lens proteins undergo oxidation and truncation during human senile cataractogenesis (Takemoto, 1997;Jimenez-Asensio et al, 1999). By simulating these two process in vitro, it may be possible to induce structural changes in the gammaS crystallin molecule that will facilitate deamidation of asparagine-143 via a molecular mechanism that is analogous to the deamidation described in this report.…”
Section: Discussionmentioning
confidence: 96%
“…The described modifications to this family of proteins include: *The proteases trypsin, subtilisin, and elastase were chosen because they consistently produced peptides with different specificity resulting in high total sequence coverage by tandem mass spectrometry. truncation of N and C termini (30)(31)(32)(33)(34), deamidation (35)(36)(37), racemization (38), phosphorylation (33,35,39), oxidation (33,37,38,40), acetylation (41,42), carbamylation (43), disulfide formation (35,44), and glycation (42). Finally, because these proteins are long lived, they are prone to adventitious modification; therefore, it is necessary to have the ability to survey many possible modifications during a single experiment.…”
Section: Mapping Protein Modification Sites In Human Lens Tissue Withoutmentioning
confidence: 99%